Grouting effect evaluation of fractured rock mass based on borehole televiewer observation. Issue 2 (October 2021) - Han, Zengqiang; Chen, Shuangyuan; Wang, Chao; Wang, Chuanying; Hu, Sheng
Abstract: Grouting is a common means to improve the strength and anti-seepage performance of fractured rock mass. Due to crack concealment, evaluating the grouting effect is a critical problem. An evaluation method of the grouting effect based on borehole televiewer observation is proposed. The optical image of the borehole wall is obtained using a borehole televiewer observation, and the fracture-filling characteristics in the measured image are recognized. The evaluation index is established based on the number of filled and unfilled cracks, defined as the borehole fracture-filling index (BFFI). By analyzing the relationship between BFFI and packer permeability test results, the evaluation standard based on BFFI is established. The evaluation method is applied to a grouting test of a hydropower station's fractured rock mass. The results show that (1) the grouting effect evaluation results of the packer permeability test and BFFI methods correlate well. (2) The grouting effect evaluation method not only visually shows the filling characteristics of grouting but also quantifies the grouting effect.